2018
DOI: 10.1016/j.polymertesting.2018.03.030
|View full text |Cite
|
Sign up to set email alerts
|

A UV-Vis spectroscopic method for monitoring of additive particle properties during polymer compounding

Abstract: Determination of the dispersion characteristics/or morphology of additives in polymer melts by fast, reliable and accurate on-line methods is highly desired in the polymer industry. An ultraviolet-visible (UV-Vis) spectroscopic methodology is described which meets these demands. It is demonstrated that the applied methodology may be developed on a cheap, packaging grade of Polylactic Acid (PLLA), an important bioresorbable polymer for the medical device industry, and still be accurate when implemented on a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…As described above, a few studies have been reported in which the transferability of machine learning models was studied in HME processes. Whitaker et al [ 31 ] studied the transferability of PLS and LDA calibration models for monitoring filler particle size in different grades of PLA (packaging and medical grade). They achieved good model transferability, attributed to the similar optical properties of the melt in each case.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As described above, a few studies have been reported in which the transferability of machine learning models was studied in HME processes. Whitaker et al [ 31 ] studied the transferability of PLS and LDA calibration models for monitoring filler particle size in different grades of PLA (packaging and medical grade). They achieved good model transferability, attributed to the similar optical properties of the melt in each case.…”
Section: Discussionmentioning
confidence: 99%
“…Whitaker et al [ 31 ] used PLS and linear discriminant analysis (LDA) (a classification algorithm) with UV–Vis spectroscopy to monitor the particle size (D50) of β-TCP (beta-tricalcium phosphate (Ca 3 (PO 4 ) 2 ) extruded in a packaging grade PLA. Two different particle sizes of β-TCP (5 and 30 µm) were used and processed separately.…”
Section: Application Of Pls For In-process Monitoring Of Critical Quality Attributes (Cqas)mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 13 ] Whitaker et al used UV–VIS spectroscopy in combination with a chemometric algorithm to measure the particle size of additive particles in polymer extrusion. [ 14 ] Becker et al used a spectroscopic sensor and turbidimetric measurement to determine the size distribution of clay particles in polypropylene/clay blends, and the width and median particle radius of the particle size distribution function agreed with the result measured by SEM. [ 15 ] Barnes et al used FT‐NIR to determine the inorganic filler concentration in polymer melts during extrusion with the error of 0.27 wt%.…”
Section: Introductionmentioning
confidence: 87%